2017
DOI: 10.1007/s12664-017-0735-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sofosbuvir-based regimens in chronic hepatitis C patients on dialysis

Abstract: Sofosbuvir-based regimens can be used in ESRD patients on dialysis with good efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 10 publications
1
31
0
1
Order By: Relevance
“…In the former study 66% of patients received daily RBV and 27% received daily SOF dose, whereas our haemodialysis patients received their treatment every other day prior to haemodialysis sessions. As mentioned before many recent studies showed that lower dose of SOF is associated with lower efficacy [15][16][17][18][19][20][21] Our study has unique strengths compared to previous studies.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In the former study 66% of patients received daily RBV and 27% received daily SOF dose, whereas our haemodialysis patients received their treatment every other day prior to haemodialysis sessions. As mentioned before many recent studies showed that lower dose of SOF is associated with lower efficacy [15][16][17][18][19][20][21] Our study has unique strengths compared to previous studies.…”
Section: Discussionmentioning
confidence: 84%
“…[13][14][15][16] Though smaller doses of the drug (200 mg/d or 400 mg on alternate day) were used by some investigators, several authors showed lower SVR rates with such doses. [15][16][17][18][19][20][21] On the other hand, high efficacy and safety of full dose SOF-containing regimens in patients with severe renal impairment were also demonstrated by many investigators. 13,17,18,[22][23][24][25][26] The purpose of this study was to report the experience of using SOF-based therapy to treat a large number of HCV patients by the health authorities in Egypt, with a significant number of them having CKD.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…An attractive solution is to lower the dose of sofosbuvir, but this may not be desirable as sofosbuvir is a prodrug and the potentially decreased levels of the active metabolite GS461203 could result in decreased efficacy. Recent studies showed lower SVR rates with a lower dose of sofosbuvir (200 mg/d or 400 mg alternate day) suggesting lower dose may have lesser efficacy . In addition, Desnoyer et al, have demonstrated the safety, high efficacy and lack of accumulation of daily, full dose sofosbuvir regimens in HCV infected patients on HD compared to half dose.…”
Section: Introductionmentioning
confidence: 99%
“…Среди побочных эффектов чаще регистрирова-лись анемия (32%), инфекции (26%), нейтропения (23%), тромбоцитопения (21%), почечная недостаточ-ность (8%) [23]. Есть опыт успешного применения схемы «софосбу-вир/даклатасвир» у пациентов с терминальной почеч-ной недостаточностью, находящихся на гемодиализе [24].…”
Section: (табл 2)unclassified